1996
DOI: 10.1111/j.1601-0825.1996.tb00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte integrins in wound healing and chronic inflammation of the human periodontiurn

Abstract: Periodontal epithelium plays a critical role in protection, destruction and repair of human periodontium. During optimal repair, epithelium migrates and covers the wound surface to prevent infection and damage of the vulnerable underlying connective tissue. During periodontal destruction, junctional epithelium undergoes transformation to pocket epithelium that has quite different characteristics from junctional epithelium. In the course of periodontal disease the epithelial attachment to the tooth surface is l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 74 publications
1
26
0
1
Order By: Relevance
“…We show that Psor was required for the pro-invasive activity of avb6 and that disruption of the association of Psor with the b6 cytoplasmic tail inhibited invasion of oral SCC cells. Previously avb6 and Psor have been implicated independently in carcinoma progression and invasion (Breuss et al, 1995;Clark et al, 1996;Haapasalmi et al, 1996;Larjava et al, 1996;Jones et al, 1997;Al-Haddad et al, 1999;Regezi et al, 2002;Jiang et al, 2004;Emberley et al, 2004;Krop et al, 2005;Banerjee et al, 2005;Ralhan et al, 2008;Wang et al, 2008;Paruchuri et al, 2008;Kesting et al, 2009), and our data identify a novel pro-invasive interaction that may explain some of these previous observations. The data further suggest that inhibition of this b6-Psor association may provide a novel therapeutic target to inhibit carcinoma invasion.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…We show that Psor was required for the pro-invasive activity of avb6 and that disruption of the association of Psor with the b6 cytoplasmic tail inhibited invasion of oral SCC cells. Previously avb6 and Psor have been implicated independently in carcinoma progression and invasion (Breuss et al, 1995;Clark et al, 1996;Haapasalmi et al, 1996;Larjava et al, 1996;Jones et al, 1997;Al-Haddad et al, 1999;Regezi et al, 2002;Jiang et al, 2004;Emberley et al, 2004;Krop et al, 2005;Banerjee et al, 2005;Ralhan et al, 2008;Wang et al, 2008;Paruchuri et al, 2008;Kesting et al, 2009), and our data identify a novel pro-invasive interaction that may explain some of these previous observations. The data further suggest that inhibition of this b6-Psor association may provide a novel therapeutic target to inhibit carcinoma invasion.…”
Section: Introductionsupporting
confidence: 72%
“…However, avb6 is upregulated during processes of tissue remodelling, including wound healing, development and in many epithelial malignancies (reviewed in Thomas et al, 2006). Significantly, avb6 expression is increased in squamous cell carcinoma (SCC) cells (Breuss et al, 1995;Clark et al, 1996;Haapasalmi et al, 1996;Larjava et al, 1996;Jones et al, 1997;Regezi et al, 2002), often with the highest levels being localised at the invasive margins (Breuss et al, 1995;Jones et al, 1997;Thomas et al, 2006), suggesting that avb6 contributes to an invasive phenotype. Indeed we, and others, have shown that avb6 promotes invasion of transformed keratinocytes (Thomas et al, 2001a, b;Ramos et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The ECM that the keratinocyte interacts with determines the integrins that are activated; a 5 b 1 and a v b 6 integrins are activated on contact with fibronectin, a 3 b 1 and a 6 b 4 integrins bind to laminin-332, and a 2 b 1 integrin is a collagen receptor. 16,17 MMP expression and activity are tightly controlled during wound healing; specific MMPs are confined to particular locations in the wound and to specific stages of wound repair (Fig. 2).…”
Section: 15mentioning
confidence: 99%
“…We suggest that titanium that has been air-polished with tooth surface abrasives with large average particle diameter and high biocompatibility causes inflammation of the gingival epithelial cells and enhances the migration of white blood cells. Integrin 6 and integrin ß4 are involved in the wound healing of gingival epithelial tissue 25,26) , and are also associated with the adhesion and migration of junctional epithelium cells. Miyata et al 27) also reported that integrin 6 and integrin ß4 are involved in the epithelial boundary surface of the implant.…”
Section: Gene Expressionmentioning
confidence: 99%